The Influence of Liquidity, Profitability and Capital Structure on the Systematic Risk of Companies in the Consumer Goods Industry Sector On the Indonesia Stock Exchange - Enalia, Fransiska (ProBisnis : Jurnal Manajemen, 2025)
Research to analyze the effect of systematic risk, profitability, capital structure and liquidity on company value in companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2019-2020. The selection of samples used in this study using purposive sampling and data collection techniques using secondary data in the form of audited financial statements. Based on the established criteria, a sample of 35 companies was obtained consisting of 70 data. The data analysis methods used are descriptive statistical analysis, classical assumption test, multiple linear regression analysis, F test, t test, interaction test and hypothesis testing. The analysis was carried out using the panel data regression method using the help of Eviews 10 software. From the stages of analysis carried out, namely estimating panel data regression models, selecting the best model, testing panel data regression assumptions, testing the feasibility of selected models, and interpreting the model, conclusions were obtained that the best panel data regression approach model is the Fixed Effect Model model. The results showed that, liquidity (CR) had a negatif and insignificant effect on systematic risk variabel (BETA), profitability (ROA) had a negatif and significant effect on systematic risk (BETA) and capital structure (DER) had a positive and insignificant effect on systematic risk (BETA), and independent variables are not simultaneously effect on the dependent variable (systematic risk).